Using of Contextual Teaching and Learning Models to Improve Students Natural Science Learning Outcomes - Rusi Rusmiati Aliyyah; Dwika Resti Ayuntina; Endang Sri Budi Herawati; Muhamad Suhardi; Ismail (Indonesian Journal of Applied Research (IJAR), 2020)
This research is a Classroom Action Research which aims to determine how efforts to improve learning outcomes through the model of Contextual Teaching Learning students 5B grade in science subjects at SDN Siliwangi. The grand tour initial showed that only 35.71% or 15 students scored above the KKM with a total of 42 students. The average science score in class 5B is 60.95. This Classroom Action Research uses the Kemmis and McTaggart model which consists of planning, implementing, observing and reflecting with success indicators of 80% of students have achieved learning outcomes with a KKM score of 65 and teacher and student activeness reaching 85%. The results showed that from 3 aspects studied, namely: Student learning outcomes obtained 54.76% learning completeness in the first cycle and 76.42% in the second cycle 84.37% student activity in the first cycle and 87.50% in the second cycle. Teacher activeness was 83.34% in the first cycle and 89.58% in the second cycle The increase in the percentage of the results of the primary cycle aspects of student learning outcomes was 19.05%, 22% student and activeness13% teacher activeness. Meanwhile, in the first cycle and the second cycle, the increase in the aspects of learning outcomes was 28%, student activity 3% and teacher activity 6%.